2000
DOI: 10.1038/sj.onc.1203615
|View full text |Cite
|
Sign up to set email alerts
|

Annexin V inhibits the 12-O-tetradecanoylphorbol-13-acetate-induced activation of Ras/extracellular signal-regulated kinase (ERK) signaling pathway upstream of Shc in MCF-7 cells

Abstract: Annexin V is a Ca 2+ -dependent phospholipid binding protein. Although it has been shown to inhibit protein kinase C (PKC) in cell-free systems, its role in the intact cell is unclear. A stable MCF-7 human breast cancer cell overexpression system was established to investigate the function of annexin V. In these cells, 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced phosphorylation and kinase activity of ERK1/2 were suppressed. Morphological changes induced by TPA were reduced by annexin V overexpression as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…However, other groups (40) have shown that stimulation of PKC in COS cells led to activation of Ras and formation of Ras-Raf-1 complexes that activate Raf-1. Sato et al (56) also reported that TPA induces activation of Ras and ERK in MCF-7 cells. Consequently, we conclude that PKC is an upstream component of the Ras/MAPK signaling pathway in primary BMC cultures.…”
Section: Discussionmentioning
confidence: 95%
“…However, other groups (40) have shown that stimulation of PKC in COS cells led to activation of Ras and formation of Ras-Raf-1 complexes that activate Raf-1. Sato et al (56) also reported that TPA induces activation of Ras and ERK in MCF-7 cells. Consequently, we conclude that PKC is an upstream component of the Ras/MAPK signaling pathway in primary BMC cultures.…”
Section: Discussionmentioning
confidence: 95%
“…In general, annexins have been implicated in the maintenance of calcium homeostasis, signal transduction, receptor-mediated endocytosis, cell proliferation and growth, ion channel formation, and the secretion of neurotransmitters and hormones (34,35). AxV, in particular, has been implicated in regulating cell proliferation (36) and as a protein kinase C inhibitor (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…A PMA-stimulated externalization of anxA5 from alveolar type II cells has been previously shown by Sohma et al (47). In our case, THP-1 cells might be releasing anxA5 during PMA stimulation as a self-defense mechanism for it has been shown that anxA5 may inhibit phorbol ester-activated pathways (48). Other stress situations have been described that cause a change in anxA5 localization.…”
Section: Discussionmentioning
confidence: 99%